Ameliorative potential of α-tocopherol against flubendiamide and copper-induced testicular-insult in Wistar rats. (25th December 2016) - Mandil, Rajesh; Rahal, Anu; Prakash, Atul; Garg, Satish K.; Gangwar, Neeraj K.; Swain, Dilip K.
Abstract: Study was undertaken to evaluate ameliorative potential of α-tocopherol against copper sulphate and flubendiamide alone and in combination-induced toxicity in rats following 90 days exposure. Absolute and relative organ weights did not differ between treatments groups. Increase of LPO in copper and flubendiamide intoxicated rats but modest increase in copper + flubendiamide group. GSH and activities of SOD, GPx and GST showed moderate decrease in intoxicated groups. Reduced CAT activity in alone exposed groups was observed. ACP, ALP and SDH remain unaltered. Increase in LDH, γ-GT, abnormal sperm and reduced 17β-HSD, percent live and HOST +ve sperms and testosterone level was observed in all three exposed groups. Xenobiotics alone and in combination exhibited degenerative germinal epithelium, necrotic germ cells, loss of spermatozoa and spermatids. Treatment with α-tocopherol, reparative potential was observed as values of most of the parameters including testicular histoarchitecture were restored. Highlights: Flubendiamide and copper alone and in combination induced oxidative stress. Both xenobiotic alone and in combination induced testicular degeneration. Combination of xenobiotics did not show additive or synergistic effect. Copper was more toxic than flubendiamide. α-tocopherol ameliorated oxidative damage and testicular damage.